PERBAIKAN PROSES PENGADAAN BARANG/JASA PADA INSTANSI LOKAL DENGAN TRANSPARANSI DAN EFISIENSI BIAYA - Uning Heri Gagarin; Jumadiah Wardati; Elia Agus Victoria (Jurnal Industri Kreatif dan Inovatif, 2025)
This PkM program focuses on improving the procurement process of goods/services in local agencies to make it more transparent, accountable, and cost-efficient. Common problems include unplanned needs, non-uniform procurement documents, poorly documented supplier selection, repetitive purchases without standardized specifications, weak acceptance controls, and slow realization reporting. Interventions are carried out through as-is process mapping, waste and risk analysis, preparation of SOPs and document templates, strengthening price comparison mechanisms and supplier evaluations, and training procurement implementers. Outputs include end-to-end procurement SOPs, specification/standard catalogs, monitoring dashboards, and recommendations for savings and internal controls.